Marcadores funcionais da atividade elétrica do córtex cerebral para identificar atrasos no desenvolvimento de funções executivas no córtex pré-frontal em adolescentes - MIRANDA, Daisy Silva (Universidade Federal do Pará, 2019)
Human cognition results from the interaction among genetic, epigenetic and environmental factors. Several studies have shown that the prefrontal cortex (CPF) is a critical region for human intelligence. This region has a long maturation period that ends in early adulthood. Previous studies have shown that the amplitude of high frequency waves recorded by resting-EEG correlates inversely with the degree of maturation of cortical circuits. The main objective of this study is to evaluate the correlation between the power of different EEG frequency bands with the performance on the WISC-IV scale (Wechsler Intelligence Scale for Children), which measures intellectual capacity, in adolescents. Subjects (N = 23) aged 12-16 years and 11 months underwent resting-EEG recordings for 5-10 minutes and were subsequently tested with the WISC-IV scale. Our results show that alpha power correlates negatively with IMO in parietal (RH and LH), occipital (RH and LH), and central (RH) regions. The IQ correlates negatively with alpha power in the temporal (RH), parietal (RH and LH), occipital (RH and LH), and central (RH) regions. Theta power correlates negatively with WM and IQ in temporal (LH), parietal (RH and LH), and occipital (RH and LH) regions. In genre analysis we observed that the correlation between power in the alpha and theta bands and cognitive indices occurs in both hemispheres for females, but not males